New clinical research strategies in thoracic oncology: clinical trial design, adaptive, basket and umbrella trials, new end-points and new evaluations of response - Jessica Menis; Baktiar Hasan; Benjamin Besse (European Respiratory Review, 2014)
In the genomics era, our main goal should be to identify large and meaningful differences in small, molecularly selected groups of patients. Classical phase I, II and III models for drug development require large resources, limiting the number of experimental agents that can be tested and making the evaluation of targeted agents inefficient. There is an urgent need to streamline the development of new compounds, with the aim of identifying “trials designed to learn”, which could lead to subsequent “trials designed to conclude”. Basket trials are often viewed as parallel phase II trials within the same entity, designed on the basis of a common denominator, which can be a molecular alteration(s). Most basket trials are histology-independent and aberration-specific clinical trials. Umbrella trials are built on a centrally performed molecular portrait and molecularly selected cohorts with matched drugs, and can include patients’ randomisation and strategy validation. Beyond new designs, new end-points and new evaluation techniques are also warranted to finally achieve methodology and clinical improvements, in particular within immunotherapy trials.